2020
DOI: 10.1007/s00431-020-03801-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in children and adolescents: a systematic review of critically unwell children and the association with underlying comorbidities

Abstract: Data show that children are less severely affected with SARS-Covid-19 than adults; however, there have been a small proportion of children who have been critically unwell. In this systematic review, we aimed to identify and describe which underlying comorbidities may be associated with severe SARS-CoV-2 disease and death. The study protocol was in keeping with Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. A total of 1726 articles were identified of which 28 studies ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
131
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(153 citation statements)
references
References 36 publications
12
131
1
9
Order By: Relevance
“…Several comorbidities have been associated with poor outcomes in adults, 35 including chronic respiratory and cardiac diseases, but these remain unclear for children. 7,18,28,36,37 Comorbidities were frequent in our cohort (29%, n=114), but these comorbidities were not independently associated with severe evolution, and accounted for only 22 severe cases of hospitalization on a national-scale. These observations may also help policy makers allow for standard school activities for these populations and help physicians to reassure families in this process.…”
Section: Discussionmentioning
confidence: 67%
“…Several comorbidities have been associated with poor outcomes in adults, 35 including chronic respiratory and cardiac diseases, but these remain unclear for children. 7,18,28,36,37 Comorbidities were frequent in our cohort (29%, n=114), but these comorbidities were not independently associated with severe evolution, and accounted for only 22 severe cases of hospitalization on a national-scale. These observations may also help policy makers allow for standard school activities for these populations and help physicians to reassure families in this process.…”
Section: Discussionmentioning
confidence: 67%
“…The results of an overview study published in May have been confirmed by several recent systematic reviews from several countries (11,12,17). The surveys show that a high proportion of children who became seriously ill and were on a ventilator had other underlying diseases (18), most commonly heart disease.…”
Section: Symptoms and Morbidity Among Children And Teenagersmentioning
confidence: 69%
“…An overview of studies documenting a total of 108 patients under 18 with a serious progression of COVID-19 indicates that there may be a correlation between underlying diseases and COVID-19 in children, i.e. the severity of the disease (18). According to the survey and data from 48 patients under the age of 18 with severe disease progression of COVID-19, 75 percent had an underlying diseases.…”
Section: Risk Groups For More Serious Covid-19mentioning
confidence: 99%
“…7 107-109 However, intriguingly, even children with serious medical conditions, who are on immunosuppressive or cancer treatment, are much less affected by COVID-19 than adults. [110][111][112][113]…”
Section: Comorbiditiesmentioning
confidence: 99%